A lens on deaf identities - Leigh, Irene W., ....- (Oxford : Oxford University Press, 2009)
The last couple of decades have witnessed an explosion of self-and-identity-related literature, spurred in large part by the rapid growth of cultural, racial, and ethnic diversity in the population of the United States, the desire to better understand the interface between identity and social groups, and the question of whether confronting differences brings about changes in self-representation. Much of this literature has, however, often overlooked the fact that diversity encompasses other domains, including disabilities such as deafness. A Lens on Deaf Identities fills this gap by exploring identity formation in deaf persons. How a deaf person develops in societies or groups with preconceived notions of disability, deafness, and what is best for deaf people has implications not only for the psychological well being and self-esteem of the deaf person, but also for what a deaf identity really means, and who decides that identity. The issue of identify formation amongst this population is fraught-even the terminology used to describe people with deafness or hearing loss contradicts the notion of a single 'deaf experience'-Deaf, deaf, oral deaf, Oral Hearing Loss, hearing impaired, acquired hearing loss, deaf with a 'hearing mind', and so on. The book explores the major influences on deaf identity, including the relatively recent formal recognition of a Deaf culture, the different internalized models of disability and deafness, the appearance of deaf identity theories in the psychological literature, the presence of greater racial and ethnic diversity in deaf individuals, technology (such as the cochlear implant) that strongly affects the identity of deaf people, and deaf people's ongoing experiences of stigma and oppression. A Lens on Deaf Identities will appeal to student and professional researchers in deaf studies and deaf education.
Keywords: Doofheid